Creative destruction in the Australian videogames industry. Issue 1 (August 2016) - Banks, John; Cunningham, Stuart
The Australian games industry is a textbook case in creative destruction. Australian developers have adaptively engaged with the rapidly transforming and uncertain conditions of the global videogames industry. Some developers celebrate the creative freedom they experienced with a shift towards original intellectual property games for mobile platforms, while others caution about the design and craft compromises associated with the in-app monetisation mechanics. The turmoil and rapidly transforming Australian videogames industry over the past few years is certainly characterised by precarious labour. But it also includes experimentation in studio culture and associated changes in professional developer identity so as to continue the craft of making videogames in the midst of this uncertainty. This diversity is also characterised by differences among the production cultures of Melbourne, Brisbane and Sydney that are indicators of the cultural roots that sustain developer identity and business models.